Адміністративна відповідальність юридичних осіб: деякі проблеми правового регулювання - Комзюк, А. Т.; Komziuk, A. T.; Липій, Е. А.; Lypii, Ye. A.; Anatolii Komziuk (Право і безпека. – 2017. – № 2 (65). – С. 34–38, 2017)
Визначено проблеми правового регулювання адміністративної відповідальності юридичних осіб, а також можливі шляхи їх вирішення. Зроблено висновок, що, пройшовши шлях від заперечення самої можливості притягнення до адміністративної відповідальності юридичних осіб до визнання їх суб’єктами цієї відповідальності в кількох окремих законах, законодавство про адміністративні правопорушення у своєму розвитку має пройти наступний етап – визначити загальні правила та процедури адміністративної відповідальності юридичних осіб, без чого неможливо забезпечити належний захист цих осіб від неправомірного притягнення до відповідальності. У зв’язку з тим обґрунтовано необхідність прийняття нового Кодексу про адміністративні проступки, в якому ці питання має бути комплексно вирішено, що сприятиме забезпеченню законності цієї відповідальності.

The problems of legal regulation of administrative liability of legal entities, as well as possible ways of their solution, have been determined. Attention is drawn to the fact that there is a tendency to constant increase of misdemeanor’s number, cases of which are considered by judges. Accepting the fact that administrative liability are less and less distinguished by administrative procedure of implementation, it is noted that it means one thing – it simply needs to be made administrative again, for which all the offenses for which penalties are imposed in court should be determined as felonies. It has been concluded that after passing the way from the denial of the even possibility of bringing legal entities to administrative liability to recognizing them as subjects of this liability in several separate laws, the legislation on administrative offenses in its development should go through the next stage – to determine general rules and procedures for administrative liability of legal entities, without which they can not be protected against unlawful prosecution. In this regard, the author has grounded the necessity of adopting a new Code on Administrative Offenses, which should comprehensively resolve these issues that will contribute to ensuring the legality of this liability.

Определены проблемы правового регулирования административной ответственности юридических лиц, а также возможные пути их решения. Сделан вывод, что, пройдя путь от отрицания самой возможности привлечения к административной ответственности юридических лиц к признанию их субъектами этой ответственности в нескольких отдельных законах, законодательство об административных правонарушениях в своем развитии должно пройти следующий этап – определить общие правила и процедуры административной ответственности юридических лиц, без чего невозможно обеспечить надлежащую защиту этих лиц от неправомерного привлечения к ответственности. В связи с этим обоснована необходимость принятия нового Кодекса об административных проступках, в котором эти вопросы должны быть комплексно решены, что будет способствовать обеспечению законности этой ответственности.
Административная ответственность юридических лиц: некоторые проблемы правового регулирования
Administrative liability of legal entities: certain problems of legal regulation
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративна відповідальність; юридичні особи; правове регулювання; адміністративні стягнення; підстави застосування; процедура; administrative liability; legal entities; legal regulation; administrative penalties; application; grounds of legal liability; procedures; административная ответственность; юридические лица; правовое регулирование